2023
DOI: 10.1001/jamapediatrics.2023.3643
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time and Developmental Performance Among Children at 1-3 Years of Age in the Japan Environment and Children’s Study

Midori Yamamoto,
Hidetoshi Mezawa,
Kenichi Sakurai
et al.

Abstract: ImportanceIt is unclear whether increased television (TV) and DVD viewing in early childhood from age 1 year decreases development or whether poor development increases TV/DVD viewing.ObjectiveTo investigate the directional association between TV/DVD screen time and performance on developmental screeners in children aged 1 to 3 years.Design, Setting, and ParticipantsThis longitudinal cohort study analyzed data from 57 980 children and mothers from a national birth cohort, the Japan Environment and Children’s S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Of note, our article was corrected to fix an error in the Meaning section of the key points. The text inadvertently read, “In this study, increased screen time in early childhood was negatively associated with poor performance on developmental screeners.” This association was not negative.…”
mentioning
confidence: 99%
“…Of note, our article was corrected to fix an error in the Meaning section of the key points. The text inadvertently read, “In this study, increased screen time in early childhood was negatively associated with poor performance on developmental screeners.” This association was not negative.…”
mentioning
confidence: 99%
“…These studies on genetic risk suggest the possibility that long screen time is a characteristic of children with developmental delays . Under such circumstances, Yamamoto et al published a study that examined the associations between screen time and children’s development, focusing on the direction of the association by the random-intercept cross-lag panel model. This research is important because it replicates and updates the results of the study by Madigan et al In particular, we are interested in the finding of Yamamoto et al that bidirectional associations were found only in the communication domain of the 5 developmental domains investigated.…”
mentioning
confidence: 99%
“…Under such circumstances, Yamamoto et al published a study that examined the associations between screen time and children’s development, focusing on the direction of the association by the random-intercept cross-lag panel model. This research is important because it replicates and updates the results of the study by Madigan et al In particular, we are interested in the finding of Yamamoto et al that bidirectional associations were found only in the communication domain of the 5 developmental domains investigated. These results support our previous findings, which highlighted that the associations between screen time and child development should be examined by developmental domain …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Original Investigation titled “Screen Time and Developmental Performance Among Children at 1-3 Years of Age in the Japan Environment and Children’s Study,” published in the November 2023 issue, there was an error in the Key Points. The Meaning section was updated to read, “In this study, increased screen time in early childhood was associated with poor performance on developmental screeners, suggesting the need to support parents in creating family media plans.” This article was corrected online …”
mentioning
confidence: 99%